Chaos Image Encryption Methods: A Survey Study - Sabah Fadhel; Mohd Shafry; Omar Farook (Institute of Advanced Engineering and Science, 2017)
With increasing dependence on communications over internet and networks, secure data transmission is coming under threat. One of the best solutions to ensure secure data transmissions is encryption. Multiple forms of data, such as text, audio, image, and video can be digitally transmitted, nowadays images being the most popular and old encryption techniques such as: AES,DES,RSA etc., show low security level when used for image encryption. This problem was resolved by using of chaos encryption which is an acceptable form of encryption for image data. The sensitivity to initial conditions and control parameters make chaos encryption suitable for image applications. This study discusses various chaos encryption techniques.